2013
DOI: 10.1271/bbb.130367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Lectins on the Transport System of Human Intestinal Caco-2 Cell Monolayers

Abstract: The effects of 16 lectins isolated from foodstuff on the transport system across human intestinal Caco-2 cell monolayers were investigated by using four fluorescent markers: lucifer yellow (LY) for the paracellular pathway, fluorescein (FL) for the monocarboxylic acid transporter-mediated pathway, rhodamine 123 for the P-glycoprotein-mediated efflux pathway, and calcein for the multidrug resistance associated protein-related efflux pathway. The transepithelial electrical resistance (TER) values for the monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In addition, the transcellular transport of WGA-functionalized nanoparticles was reported to occur in a cytoskeleton-dependent manner and mainly via a clathrin-mediated mechanism [23]. However, in this study, less WGA than RBA1 was transported across Caco-2 cell monolayers, although WGA showed strong effects on the transport system of the cell monolayers [7]. We have no explanation for this phenomenon at present.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, the transcellular transport of WGA-functionalized nanoparticles was reported to occur in a cytoskeleton-dependent manner and mainly via a clathrin-mediated mechanism [23]. However, in this study, less WGA than RBA1 was transported across Caco-2 cell monolayers, although WGA showed strong effects on the transport system of the cell monolayers [7]. We have no explanation for this phenomenon at present.…”
Section: Discussionmentioning
confidence: 62%
“…Although its usefulness and nutritional potential are well known, it is largely discarded or used as animal feed or fertilizer [15]. Numerous recent studies have revealed that lectins from foodstuffs or traditional herbal medicines have many interesting biological functions including immunomodulating effects [16], selective cytotoxicity against cancer cells [17], anti-microbial and insecticidal activity [18], and modulating effects on the intestinal transport system [7]. In addition, many lectins are currently used as important tools in the fields of biochemistry, cell biology and immunology, as well as for diagnostic and physiologic purposes in cancer research; furthermore, they have been used as therapeutic agents in clinical trials [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that garlic (A. sativum) lectin maintained its activity in the intestines and activated immunoreactivity when orally administered to mice (Clement et al, 2010). We have shown that lectins contained in foodstuff had modulating effects on the transport system of human intestinal Caco-2 cell monolayers (Ohno et al, 2006;Yamamoto et al, 2013;Nemoto et al, 2015). Thus, plant lectins can be considered as physiologically active ingredients in food resources.…”
Section: Discussionmentioning
confidence: 82%
“…Wheat germ agglutinin (WGA) was found to be capable of increasing permeability of the gastrointestinal epithelium to allow the traversing of molecules with a size at least up to 3 kDa and this result supported its suitability as a carrier for oral drugs [17]. Besides, some other lectins/hemagglutinins isolated from dietary sources were also demonstrated to be capable of modulating the intestinal transepithelial transport system [18,19].…”
Section: Discussionmentioning
confidence: 89%